2021
DOI: 10.1080/17441692.2021.1876751
|View full text |Cite
|
Sign up to set email alerts
|

Primary care perspectives on pandemic politics

Abstract: While the COVID-19 pandemic now affects the entire world, countries have had diverse responses. Some responded faster than others, with considerable variations in strategy. After securing border control, primary health care approaches (public health and primary care) attempt to mitigate spread through public education to reduce personto-person contact (hygiene and physical distancing measures, lockdown procedures), triaging of cases by severity, COVID-19 testing, and contact-tracing. An international survey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…Countries that have fared the best are the ones with good governance and public support [49]. Countries with an absence of coherent leadership and social trust have worse outcomes than countries with collective action, whether in a democracy or autocracy, and rapid mobilisation of resources [50]. The erosion of trust in the United States government has hurt the country's ability to respond to the COVID-19 crisis [51,52].…”
Section: Heterogeneity Of the Pandemic Among Countries With High Hdi:...mentioning
confidence: 99%
“…Countries that have fared the best are the ones with good governance and public support [49]. Countries with an absence of coherent leadership and social trust have worse outcomes than countries with collective action, whether in a democracy or autocracy, and rapid mobilisation of resources [50]. The erosion of trust in the United States government has hurt the country's ability to respond to the COVID-19 crisis [51,52].…”
Section: Heterogeneity Of the Pandemic Among Countries With High Hdi:...mentioning
confidence: 99%
“…PHC comprises both population-level public health and individual-based primary care, as well as community-based social services (Muldoon et al, 2006). An international study found that in most countries, public health and primary care were insufficiently integrated for an effective epidemic response (Goodyear-Smith et al, 2021). For example, a coordinated approach to COVID-19 swabbing and contact-tracing of positive cases was often lacking.…”
mentioning
confidence: 99%
“…[49] Countries with an absence of coherent leadership and social trust have worse outcomes than countries with collective action, whether in a democracy or autocracy, and rapid mobilisation of resources. [50] The erosion of trust in the United States government has hurt the country's ability to respond to the COVID-19 crisis. [51,52] The editors of the New England Journal of Medicine argued that the COVID-19 crisis has produced a test of leadership;…”
Section: Resultsmentioning
confidence: 99%
“…[54,55] Countries with health systems and policies that are able to integrate International Health Regulations (IHR) core capacities with primary health care (PHC) services have been effective at mitigating the effects of COVID-19. [50,53] Australia has been able to control its COVID-19 epidemic through a comprehensive primary care response (including protection of vulnerable people, provision of treatment and support services to affected people, continuity of regular healthcare services, protection and support of PHC workers and primary care services, and provision of mental health services to the community and the primary healthcare workforce).…”
Section: Resultsmentioning
confidence: 99%